Toxicological Assessment of Lead Nitrate on Lumbricus terrestris: Behavioral and Biochemical Implications - Hanna, Nihal S. Hanna S.; Shekha, Yahya A. Shekha A. (Sulaimani Journal for Humanities, 2025)
During the study, individuals of the earthworm Lumbricus terrestris were exposed to various levels of lead (II) nitrate at different times. The soil and earthworm samples were collected from local orchards within the Shaqlawa district. Soil samples were tested for physical and chemical characteristics, including pH, Electrical conductivity (EC), soil moisture content, organic matter, and texture. The studied organisms were exposed to variable concentrations of lead nitrate, ranging from 0 to 5000 ppm. Also, the lead concentrations in the soil and the earthworm body were measured. Earthworms collected from the experimental media were tested for biochemical markers, including acetylcholinesterase (AChE), glutathione S-Transferase (GST), catalase (CAT), and malondialdehyde (MDA). After 96 hours, the lethal concentration (LC50) was estimated to be 4723.45 ppm. The findings on behavior revealed that lead altered morphology, and the behavior of treated individuals was compared to that of the controls. Lead concentration increased within the worm’s body as the soil lead level decreased. The value of AChE was inversely related to lead concentration. However, GST, CAT, and MDA increased with lead exposure
Keywords: Lead nitrate; Earthworm; LC50; Behavioural and Biochemical